The Influence of Brand Image and Quality of Tolak Angin Sidomuncul Products on the People of Kediri Regency - Nur Alivia, Issabela Tetania (Universitas Nusantara PGRI Kediri, 2025)
This study analyzes whether there is a significant influence between brand image variables and product quality simultaneously or partially on the purchase decision of Tolak Angin Sidomuncul. This research aims to show the influence of brand image and product quality on purchase decisions. This research is a quantitative research. This research was conducted at Nur Kholis' store. The questionnaire was measured by a likert scale obtained by 40 respondents of Tolak Angin Sidomuncul customers in the Kediri regency area as a research sample selected for incidental sampling. The data obtained was analyzed with Multiple Linear Regression Analysis to be able to answer research questions. Multiple Linear Regression analysis was carried out after meeting the validity and reliability tests of classical assumption tests. From the results of the study, it was obtained that there was a significant influence between brand image variables and product quality simultaneously or partially on the purchase decision of Tolak Angin Sidomuncul. Brand image and product quality are considerations for consumers when buying a product. This study provides implications from brand image and product quality how influential it is on purchasing decisions. This study only discusses the influence of brand image and product quality on purchasing decisions, as well as too small a number of samples studied.